Multiplex coherent anti-Stokes Raman microspectroscopy with tailored Stokes spectrum - Rehbinder, Jean; Pohling, Christoph; Buckup, Tiago; Motzkus, Marcus (Optics letters, 2010)
We combined the ultrabroadband supercontinuum of a photonic crystal fiber with a pulse shaper, resulting in a highly flexible light source for multiplex coherent anti-Stokes Raman microscopy. Implemented as the Stokes pulse, it provides tailored selection of the relevant Raman transitions, resulting in a reduced photon load and partial suppression of the nonresonant background. This experiment exploits the advantages of multiplex excitation with the increased acquisition speed of single-channel detection. The molecule-specific Stokes pulses are demonstrated for chemical mapping of a polymer blend.
Gesehen am 12.05.2023